Straight talk on investing : - Brennan, Jack (J. Wiley, 2002)
This gem of an investment guide packs into 200 pages everything an individual needs to know to make informed savings and investment decisions. The advice is elegantly simple, eminently sensible, and delightfully readable. Straight Talk belongs on every investor’s bookshelf